Malawi : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Malawi. - International Monetary Fund. African Dept. (Washington, D.C. : International Monetary Fund, 2020)
Presidential elections in June 2020, a re-run of the canceled 2019 elections, resulted in a change of government, with President Chakwera securing 59 percent of the vote. The new administration is facing a rapid acceleration of COVID-19 cases in Malawi and adverse spillovers from continued deterioration of the global and regional economic situation, significantly worsening the macroeconomic outlook. Consequently, an additional urgent balance of payments need of 2.9 percent of GDP has arisen-bringing the total external financing gap in 2020 to 5.0 percent of GDP. The authorities have requested an additional disbursement of 52.1 percent of quota (SDR 72.31 million) under the 'exogenous shock' window of the Rapid Credit Facility (RCF), where 30 percent of the disbursement would finance the government budget. This follows the May 1, 2020 Board approval of a 47.9 percent of quota RCF disbursement (without budget support). The authorities have cancelled the Extended Credit Facility (ECF) and expressed a strong interest in discussing a new ECF-better aligned with their new long-term growth and reform strategy-once conditions permit.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet